IMPLEMENTATION OF THE VISUAL DICTIONARY ON TEXTILE AND FASHION INTO THE MOBILE APPLICATION - ZAKHARKEVICH, OKSANA; KOSHEVKO, JULIA; ELNASHAR, ELSAYED; SHVETS, GALINA; SELEZNEVA, ANNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article reveals the essence of mobile applications as one of the modern education methods in higher education among students majoring in clothing design. The paper described implementing the existing form of a book dictionary into the mobile application as a customized visual dictionary that meets the national guidelines' requirements and the learning outcomes declared in them. The article substantiates the content of the conceptual and categorical apparatus of the mobile application (dictionary) for students majoring in clothing design. It proves the effectiveness of its use in the educational space.
Keywords: mobile learning; mobile application; visual dictionary; mobile education